IMPROVING STUDENTS’ LISTENING SKILL BY USING DICTOGLOSS TECHNIQUE (A Classroom Action Research to the Tenth Grade Students of SMA Abdi Agape in the Academic Year of 2019/2020) - - Alponiyati; Desi Sri Astuti; Sahrawi - Sahrawi (XXXX-XXXX, 2020)
This research was conducted in order to know how Dictogloss Technique improve students’ listening skill on descriptive text. This research was done by using Classroom Action Research. It was carried out with the tenth grade students of SMA Abdi Agape in the academic year of 2019/2020. The subject of this research was science X IPS class which consist of 9 students. The instruments used to collect the data were field note, observation checklist table, and listening test. To analyze the data, the researcher used qualitative and quantitative data. In qualitative data, the researcher analyzed the data by using data reduction, data display, and drawing conclusion. In quantitative data, the researcher analyzed the data from the test which calculated by mean score in each cycle. The result of this research showed the improvement of students’ listening skill was successful. The researcher concluded that Dictogloss Technique improved students’ reading comprehension on recount text to the Eighth Grade Students of SMA Abdi Agape. Keywords: Listening Skill, Dictogloss Technique and Classroom Action Research.